問題文全文(内容文):
$\displaystyle
\begin{eqnarray}
\left\{
\begin{array}{l}
\frac{5}{2}x -\frac{3}{2} y = \frac{9}{2} \\
\frac{3}{4}x + \frac{9}{2}y = 3
\end{array}
\right.
\end{eqnarray}$
$\displaystyle
\begin{eqnarray}
\left\{
\begin{array}{l}
\frac{5}{2}x -\frac{3}{2} y = \frac{9}{2} \\
\frac{3}{4}x + \frac{9}{2}y = 3
\end{array}
\right.
\end{eqnarray}$
単元:
#数学(中学生)#中2数学#連立方程式
指導講師:
【楽しい授業動画】あきとんとん
問題文全文(内容文):
$\displaystyle
\begin{eqnarray}
\left\{
\begin{array}{l}
\frac{5}{2}x -\frac{3}{2} y = \frac{9}{2} \\
\frac{3}{4}x + \frac{9}{2}y = 3
\end{array}
\right.
\end{eqnarray}$
$\displaystyle
\begin{eqnarray}
\left\{
\begin{array}{l}
\frac{5}{2}x -\frac{3}{2} y = \frac{9}{2} \\
\frac{3}{4}x + \frac{9}{2}y = 3
\end{array}
\right.
\end{eqnarray}$
投稿日:2022.06.20